Optimization technique of organizational and technological structures of systems of small batch assembly of complex mechanical engineering products - Скоркін, Антон Олегович (Technology audit and production reserves, 2014)
The optimization technique of organizational-technological and technical preparation of assembly production of complex mechanical engineering products is considered in the paper. Development trends of modern assembly production consist in continuous increase in production output in terms of both nomenclature and volume and lead to the steady growth of unit man-hours of assembly operations, and, consequently, to the growth of demands for production facilities and increase in the number of workers, employed in the assembly production (especially at its final stages). As is known, the common problem of machine manufacturing consists of technological tasks, including the parts manufacturing accuracy and assembly process quality. If the first problem is solved at the optimization stage of parts machining, the second finds the solution at the final stage of machine manufacturing in conditions of assembly production technology. Labor productivity in small-batch assembly production of complex mechanical engineering products also appears to depend on subjective factors, and its level tends to periodic change. The introduction of automated design systems of assembly processes, based on simulation techniques is the effective solution to these problems. The paper gives the operation principle of the simulation system, which allows to develop the structure of technological operations, and provides a minimum assembly time of complex mechanical engineering products in small-batch production conditions.